Phase I Trial of [99mTc]Tc-maSSS-PEG2-RM26, a Bombesin Analogue Antagonistic to Gastrin-Releasing Peptide Receptors (GRPRs), for SPECT Imaging of GRPR Expression in Malignant Tumors; Cancers; Vol. 15 - iss. 6 - Chernov V. I. Vladimir Ivanovich; Rybina A. N. Anastasiya Nikolaevna; Zelchan (Zeltchan) R. V. Roman Vladimirovich; Medvedeva А. А. Anna Aleksandrovna; Bragina O. D. Olga Dmitrievna; Lushnikova N. Nadejda; Doroshenko A. Artem; Usynin E. Evgeniy; Tashireva L. Liubov; Vtorushin S. Sergey; Abouzayed A. Ayman; Rinne S. S. Sara; et al. (2023, 2023)
The gastrin-releasing peptide receptor (GRPR) is overexpressed in prostate cancer (PCa) and in hormone-driven breast cancer (BCa). The aim of this phase I clinical trial was to evaluate safety, biodistribution, and dosimetry after the administration of the recently developed GRPR-targeting antagonistic bombesin analogue [99mTc]Tc-maSSS-PEG2-RM26 in PCa and BCa patients. Planar and whole-body SPECT/CT imaging was performed in six PCa patients and seven BCa patients 2, 4, 6, and 24 h post the intravenous administration of 40 µg of [99mTc]Tc-maSSS-PEG2-RM26 (600–700 MBq). No adverse events or pathological changes were observed. The rapid blood clearance of [99mTc]Tc-maSSSPEG2-RM26 was observed with predominantly hepatobiliary excretion. The effective doses were 0.0053 ± 0.0007 for male patients and 0.008 ± 0.003 mSv/MBq for female patients. The accumulation of [99mTc]Tc-maSSS-PEG2-RM26 in tumors was observed in four out of six PCa and in seven out of seven BCa patients. In four BCa patients, a high uptake of the agent into the axillary lymph nodes was detected. Immunohistochemistry revealed positive GRPR expression in 60% of primary PCa, 71.4% of BCa tumors, and 50% of examined BCa lymph nodes. In conclusion, a single administration of [99mTc]Tc-maSSS-PEG2-RM26 was safe and well tolerated. [99mTc]Tc-maSSS-PEG2-RM26 SPECT may be useful for tumor detection in PCa and BCa patients, pending further studies.